2016
DOI: 10.1111/hiv.12411
|View full text |Cite
|
Sign up to set email alerts
|

Higher rates of triple‐class virological failure in perinatally HIV‐infected teenagers compared with heterosexually infected young adults in Europe

Abstract: ObjectivesThe aim of the study was to determine the time to, and risk factors for, triple‐class virological failure (TCVF) across age groups for children and adolescents with perinatally acquired HIV infection and older adolescents and adults with heterosexually acquired HIV infection.MethodsWe analysed individual patient data from cohorts in the Collaboration of Observational HIV Epidemiological Research Europe (COHERE). A total of 5972 participants starting antiretroviral therapy (ART) from 1998, aged < 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 20 publications
2
41
0
1
Order By: Relevance
“…Nevertheless, transition to adulthood still presents challenges for optimal HIV disease management as adolescent health needs evolve and autonomy for their own self care is necessary [17]. Many of these challenges are shared by both vertically and horizontally infected adolescents, although their disease progression and severity during adolescence may differ [18,19]. To better understand the reasons for poorer outcomes in adolescents compared to other age groups, and the contributions of the transition to adulthood as well as the potential impact of healthcare transition, consensus is needed across settings for both research and surveillance on how to recognize and define when healthcare transition has occurred and ultimately how to identify successful transition through adolescence to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, transition to adulthood still presents challenges for optimal HIV disease management as adolescent health needs evolve and autonomy for their own self care is necessary [17]. Many of these challenges are shared by both vertically and horizontally infected adolescents, although their disease progression and severity during adolescence may differ [18,19]. To better understand the reasons for poorer outcomes in adolescents compared to other age groups, and the contributions of the transition to adulthood as well as the potential impact of healthcare transition, consensus is needed across settings for both research and surveillance on how to recognize and define when healthcare transition has occurred and ultimately how to identify successful transition through adolescence to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV Research Network based in the USA reported that 20% of youth aged 21 years receiving HIV care were lost to follow-up within one year [16]. In the UK and Europe, studies of young people with perinatal HIV suggest similarly poor outcomes, with increased risk of mortality [17], care disengagement [18], and treatment failure [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…(1) Chi2 test (2) Fisher's exact test (3) Wilcoxon-Mann-Whitney test (1) Chi2 test; (2) Fisher's exact test; (3) Wilcoxon-Mann-Whitney test †More than 95% of planned doses taken. 15 [13][14][15][16][17] 16 [14][15][16][17][18] 13 [12-(1) Chi2 test; (2) Fisher's exact test; (3) Wilcoxon-Mann-Whitney test Flow chart of inclusion of 209 APHIV in the COHADO Cohort, IeDEA-pWADA, 2015.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Since 2015, universal ART is recommended by WHO [13]. Compared to adults or younger children, adolescent living with perinatally acquired HIV (APHIV) experience higher morbidity, mortality and lower rates of virological suppression on ART [3,[14][15][16]. This is most likely related to delayed access to HIV diagnosis and ART in childhood, lack of timely HIV-disclosure while growing-up, with poor medication adherence in a context of prolonged ART, poor retention in care, explained by individual, social, and structural barriers [6,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%